Evaluation of Office Ergonomic Risk Using Rapid Office Strain Assessment (ROSA) - Ester Lisnati Jayadi; Panca Jodiawan; Achmad Zaki Yamani; Muhammad Qurthuby (Universitas Bunda Mulia, 2020)
Musculoskeletal Disorders (MSDs) caused by computer use have become the most common ergonomic risks. The risk experienced can be in the form of financial losses or even lives. Therefore, efforts are needed to prevent the occurrence of ergonomic risks so as not to cause large losses. The Rapid Office Strain Assessment (ROSA) has been designed to identify ergonomic risk factors and is reliable for the assessment of office workers' MSDs. This study evaluates the potential risk of ergonomics in female office workers because a previous study found that MSDs were more common in women. From the two workers observed, it was found that workers 1 and 2 received different scores on several assessment components. The different things are the length of the seat holder, armrests, spine brace, and keyboard. This difference is caused by body posture and different types of chairs. The length of the chair and the spinal brace is influenced by the different postures of the two workers. Worker 1 has a shorter upper leg length than worker 2, so she cannot use the backbone section of the chair. Although there are differences in scores on some components of the assessment, both workers have the same final ROSA score, which is 5. This indicates that further posture assessment needs to be done using tools other than ROSA to detect the specific cause of MSDs levels.